2018
DOI: 10.30892/gtg.21121-286
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Industry Perceptions and Expectations of Tourism Students: A Case Study in Turkey

Abstract: Tourism and Hospitality Management Schools' students must complete their internship before graduation in four or five stars hotels or travel agencies in Turkey. Some students may have negative perceptions of tourism education and working conditions in the industry, after they have worked as trainees in the industry. The aim of the study is to compare the perceptions and expectations of students in relation to tourism industry who have done their internship with those who have not and is to explore the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…However, from Table 5, there was, generally, no significant difference in perceptions of students who had experienced careers in the industry and those who had not (p = 0.20). This finding is in congruence with a finding by Turanligil and Altintaş (2018) in Turkey, where both students with industry experience and those without experience generally had similar perceptions of the industry.…”
Section: Differences In Students' Perceptions Of Hospitality Careers By Sociodemographic Characteristicssupporting
confidence: 90%
See 3 more Smart Citations
“…However, from Table 5, there was, generally, no significant difference in perceptions of students who had experienced careers in the industry and those who had not (p = 0.20). This finding is in congruence with a finding by Turanligil and Altintaş (2018) in Turkey, where both students with industry experience and those without experience generally had similar perceptions of the industry.…”
Section: Differences In Students' Perceptions Of Hospitality Careers By Sociodemographic Characteristicssupporting
confidence: 90%
“…Similarly, Roney and Ötzin (2007) reported indifferent perceptions of students about careers in the industry in Turkey. On the contrary, Turanligil and Altintaş (2018) and Amissah et al (2019) found that hospitality and tourism students in Anadolu University and University of Cape Coast in Turkey and Ghana respectively had negative perceptions about careers in the industry. However, Barron et al (2007) reported positive perceptions of careers in the hospitality industry by students in United Kingdom.…”
Section: Undergraduate Students' Perceptions Of Careers In the Hospitality Industrymentioning
confidence: 97%
See 2 more Smart Citations